Design Of Information Systems For Merdeka Belajar Kampus Merdeka Services In Higher Education In Indonesia - Al Hafidz, Mohammad; Supriyanto, Heri; Prasetya, Muhammad Septama (MSJ : Majority Science Journal, 2024)
Merdeka Belajar Kampus Merdeka (MBKM) aims to provide opportunities for students to master various disciplines to prepare themselves for the world of work. One of the MBKM programs that students can take part in is an internship. Universitas Hayam Wuruk Perbanas (UHW Perbanas) is a university that is required to be able to design and implement innovative learning processes so that students can take part in internship programs. During the management of internships, problems were found, namely (1) the length of processing internship approvals, (2) data processing was less effective, efficient, fast and accurate, (3) the process of monitoring and preparing reports was not smooth, and (4) difficulties in scheduling exams. and assessment because it is done manually. This research aims to develop an internship management application using the waterfall method. In this research, the stages carried out only include conducting a needs analysis and designing a system that is used as a guide in developing web-based applications that are integrated between users. The finished application design is validated and confirmed by the user. The results show that the entire application design is in accordance with user needs.